APLIKASI TEKTONIK LEMPENG DALAM SUMBER DAYA MINERAL, ENERGI DAN KEWILAYAHAN - -, Zufialdi Zakaria (Fakultas Teknik Geologi Universitas Padjadjaran, 2007)
Indonesian Region have the condition of complicated tectonic. Indonesian Archipelago is represent meeting of Pacific Plate and Indian-Australian Plate (in Eastern Indonesia), and also Eurasia Plate and Indian-Australia Plate (in Western Indonesia), and also smaller plate ( Caroline Plate and Philippine Sea Plate).Plate boundaries can be estimated by zone of active earthquake, zone of mass movement in mountain region, zone of volcanism, zone of magmatisme, and zone of hydrocarbon.Estimation of plate tectonic boundary is important to support an investigation and research of mineral resources, energy resources, and terrain resources can be predicted. On land resources study, plates tectonic boundary is most important to anticipate of geological disaster.